The Effect of Bank Soundness Factors on Sharia Bank Performance in Indonesia - Pramesti, Diah; Damayanti, Rosita Mei (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study examines the impact of bank soundness factors on the performance of Sharia banks in Indonesia using the Risk, Good Corporate Governance, Earning, Capital (RGEC) approach. This study is quantitative research and the data analysis technique used is a multiple linear regression analysis test, with the hypothesis test used as the t-test and the F-test. The population of this study is all Sharia commercial banks in Indonesia listed in OJK during the 2017-2022 period. The sample used in this study was selected using a purposive sampling method. The study concludes that Good Corporate Governance (GCG), Return on Equity (ROE), and Operating Costs to Operating Income (BOPO) have a significant impact on net income/loss. Furthermore, all RGEC variables have a simultaneous effect on bank performance, explaining half of the impact.